Respuesta :
Multiply the number outside the parenthesis by each term inside the parenthesis:
-9 * 5j = -45j
-9 *k = -9k
−9⋅(5j+k) = -45j - 9k
Answer:
[tex]-45j-9k[/tex].
Step-by-step explanation:
The given expression is
[tex]-9\cdot (5j+k)[/tex]
We need to find the equivalent expression of given expression.
According to the distributive property,
[tex]a(b+c)=ab+ac[/tex]
Using distributive property the given expression can be rewritten as
[tex]-9\cdot (5j)-9\cdot (k)[/tex]
[tex]-45j-9k[/tex]
Therefore, the required expression is [tex]-45j-9k[/tex].